"Passing the trash" by the Michigan Board of Education - Crandall, William, 1956-; Parnell, John A. (John Alan), 1964-; Spillan, John E. ([London] : SAGE, 2016)
This case discusses the crisis that was generated by the Michigan Board of Education's decision to cover up the sexual assaults of minors committed by one of their teachers. Instead the teacher was allowed to resign quietly and was eventually rehired by another school where he was free to strike again, causing further emotional trauma and financial damage.
Originally Published in: Crandall, W. R, Parnell, J. A., & Spillan, J. E. (2013). "Passing the Trash" by the Michigan Board of Education. In Crisis management: Leading in the new strategy landscape (2nd ed., pp. 223-225). Los Angeles: SAGE Publications, Inc. ISBN: 9781412991681.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Crisis management -- Case studies; Child sexual abuse by teachers -- Michigan -- Case studies